GENE ACTION AND ORDER EFFECTS IN DOUBLE CROSS HYBRIDS GENE ACTION AND ORDER EFFECTS IN DOUBLE CROSS HYBRIDS OF MAIZE ( OF MAIZE ( OF MAIZE ( Zea mays Zea mays L.) FOR GRAIN YIELD UNDER DIVERSE AGROCLIMATIC ZONES OF TELANGANA - K. SUMALINI; T. PRADEEP; E. RAJANIKANTH, D. SRAVANI ,; REDDY, S. NARENDER (The Bioscan, 2018)
Maize is the third most important cereal crop after rice and wheat in India. Seven inbreds were utilized for crossing programme to produce twenty one single crosses and 105 each three-way and double crosses in half diallel fashion and evaluated during kharif 2015 at three locations. Quadriallel analysis was conducted to study 1-line general, 2-line, 3-line and 4-line interaction effects, gene action and order effects for grain yield of double crosses. BML-51 had the highest 1-line general effect, BML-51 × BML-14 showed highest 2-line general effect. (BML-13 × BML-7) (- -) had the highest 2-line specific effect of (ij) (- -) type and (BML-32 × -) (BML-13 × -) had the highest 2-line specific effect of (i-) (j-) type. (BML-32 × BML-14) × (BML-51 × -) had the highest 3-line specific effect of (ij) (k-) type and (BML-51 × BML-6) × (BML-14 × BML-7) had the highest 4-line specific effect of (ij) (kl) type. Cross (BML-51 × BML-14) × (BML-10 × BML-7) showed high grain yield and had high 1-line general line and 2-line general effects. Additive and additive type of epistatic interactions and additive × dominance interactions were predominant in expression of grain yield.